The STRATEGIC EFFORTS TO REDUCE DISCOMFORT IN THE IIIRD TRIMESTER OF PREGNANT WOMEN THROUGH PRENATAL YOGA CLASS IN THE WORKING AREA OF THE KAHURIPAN PUSKESMAS, TASIKMALAYA CITY - yuliastuti, santi; Khairiyah P, Ir ir (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2024)
During pregnancy, women need time to adapt to the various changes that occur within them. Physical changes, especially in the third trimester, such as frequent urination, shortness of breath, back pain, heartburn, constipation, insomnia and dyspnea cause discomfort in pregnant women. One way to overcome discomfort in the third trimester is to do exercises, namely antenatal yoga. The positive effects of yoga can reduce stress, anxiety and back pain throughout pregnancy. Therefore, researchers want to know the effect of prenatal yoga classes as a strategic effort to reduce discomfort in third trimester pregnant women through community empowerment. This research is a research method of socializing and practicing antenatal yoga for Trimester III pregnant women, carried out for 12 months, namely from January to December 2023, involving the coordinating midwife and CI of the Tamansari Community Health Center as well as 15 respondents from third trimester pregnant women. The location of the activity is in the Kahuripan Community Health Center Working Area, Tasikmalaya City. Research data was obtained, almost all pregnant women experienced discomfort during pregnancy, but after doing antenatal yoga 4 times in 20 minutes, the discomfort in pregnant women was reduced. All pregnant women felt comfortable and showed high enthusiasm for this activity and hoped that the antenatal yoga class activities could be carried out in a sustainable manner to improve the fitness and health of pregnant women.